Sistem Penilaian Kinerja Berbasis Sasaran Kinerja Pegawai (SKP) di Lingkungan Sekretariat Daerah Kota Banjarbaru - Budiawan Bimantoro Aji (Journal on Education, 2022)
The research aims to: 1) analyze performance appraisal based on Employee Performance Goals (SKP), 2) identify the supporting and inhibiting factors in performance appraisal based on Employee Performance Goals (SKP). The results of this study are: (1) The SKP-based performance assessment at the Banjarbaru City Regional Secretariat in 2020 was carried out well and the assessment process was effective. The Appraisal Officer's assessment is in accordance with the SKP-based work performance appraisal aspects in PP Number 30 of 2019. The results of this employee performance assessment can be used as a consideration for determining policies for career management of civil servants related to: 1) Field of Work, as a consideration of policies for planning the quantity and quality of human resources and designing civil servant jobs; 2) Appointment and placement, as consideration for recruitment, selection and placement of civil servants according to competence and work performance; 3) Development Sector, as a consideration of career development and the ability and skills of civil servants with career patterns and organizational training programs; 4) Award Division, as consideration for awarding work performance-based awards such as promotions, salaries, work performance allowances, promotions or other compensation. 2) Implementation of the SKP-based PNS performance appraisal policy supported by a work planning system sourced from the Banjarbaru City Government's strategic plan; implementation of policies according to regulations; benefits received by the target group from employee performance appraisal activities; scope of changes desired from employees according to regulations; procedures for evaluating the work performance of civil servants according to the rules; and there is oversight of the policy process according to regulations.